Influence of the number of assessed lymph nodes on the quality of N stage assessment in radically treated patients with colon cancer - Świątoniowski, Grzegorz; Brużewicz, Szymon; Kuniej, Tomasz; Suder, Elżbieta; Kłaniewski, Tomasz; Molenda, Włodzimierz (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: Stage of the disease is the most important prognostic factor in colon cancer, and therefore should be precisely determined. Aim of the study: The aim of this study was to determine the influence of the number of assessed lymph nodes on the quality of the N stage assessment in radically treated patients with colon cancer. Material and methods: 144 patients with nose-positive colon cancer treated with adjuvant chemotherapy in years 1999–2007 in the Military Hospital in Wrocław. Elective (n=100) or emergency (n=14) surgery was performed in the specialist surgery centre (n=97) and regional surgery department (n=17) in years 1999 – 2003 (n=62) and 2004 – 2007 (n=52). Results: The number of assessed lymph nodes was between 1 and 29 (average – 4.8; median – 3.5). In the majority of cases only a few lymph nodes were examined: one (14%), two (14.9%) three (21%) or four (13.1%). 12 or more lymph nodes (which is required in the TNM classification) were assessed only in 7 patients (6.1%). A statistically significant (p=0.004) relationship between the number of assessed lymph nodes and type of surgery centre was confirmed (specialist centre – average 5.1 lymph nodes, regional surgery departments – average 2.9 lymph nodes). Conclusions: In the majority of patients fewer lymph nodes are assessed than is needed to differentiate between stage N1 and N2. More lymph nodes were assessed in specialist surgical centres, which suggests better quality assessment of the N stage.